CASTANHO, Sandra Maria. Lei, trabalho e política no Brasil. Lutas sociais e reforma agrária (1945-1964). Maringá: Eduem, 2009. (Dialogos, 2017)
CASTANHO, Sandra Maria. Lei, trabalho e política no Brasil. Lutas sociais e reforma agrária (1945-1964). Maringá: Eduem, 2009.